Fintech-Based Accounting Recording Training For MSME Actors: Native Papuan Mothers Selling Betel Nutcrackers In Entrop Ward, Jayapura City - Pascalina V. . S. Sesa; Meinarni Asnawi (International Journal Of Community Service, 2025)
Rapid technological advances provide opportunities for MSME actors to improve services to customers through digital platforms, such as e-commerce. The use of technology in the online buying and selling system not only expands the market, but also has the potential to increase business income. Unfortunately, many MSME actors still do not understand how to optimize digital technology for their business development. This lack of understanding is an obstacle to implementing accounting information systems integrated with fintech, thus hindering business growth. To overcome these challenges, the community service program in Entrop Ward, Jayapura City, is designed to increase financial literacy for MSME actors, especially native Papuan mothers who sell areca nuts. This activity includes education and practical training related to financial management and the use of financial technology in recording business transactions. With this program, participants are expected to be more independent in managing finances and optimizing technology to support the development of their businesses. A total of 16 participants, who are areca nut sellers, participated in this activity. The results of the evaluation showed an increase in their understanding of financial records, both manually and through the Buku Warung application. These findings confirm that an educative approach and practice-based training are effective in helping MSME actors understand and apply financial technology for the sustainability of their businesses.